Implementation of Joint Delivery Voucher Program Through Blended Reinforcement Activity for Competency Enhancement (Project BRACE) - Dinglasan, J; Canosa, F; Orpilla, N (SAFE-Network, 2024)
The world was severely affected by the Covid-19 pandemic which brings chaos and uncertainty to everyone in society including the Education Sector. With the ongoing lockdowns and restrictions in different parts of the country, the education sector never stops pursuing to deliver the best kind of training and enhancement activities to the learners especially the Senior High School of the Technical Vocational Livelihood Track of Mataas na Paaralang Neptali A. Gonzales through Project BRACE (Blended Reinforcement Activity for Competency Enhancement). The researchers anchor this study on the selected Joint Delivery Voucher Program (JDVP) scholars as to the basis for the development of knowledge, skills, and attitudes in enhancing their competencies in Cookery. The purpose of this study is to use blended reinforcement activities through Online Distance Learning and Modular Distance Learning Approaches to assist those students who were not able to catch up on lessons due to some work, poor internet connection, and struggling students. This is in support of our School Division Mantra: “Batang Mandunong Walang Maiiwan, Lahat Kabahagi ng Bilang”. The effectiveness of the program is being measured by getting the level of performance of the respondents as revealed by their mean grades before and after the implementation of Project BRACE. The researchers collected the TVL final grades of the 32 beneficiaries of Cookery from their respective advisers and the grade given by their Work Immersion TechVoc Institution during the JDVP Program. Consolidated grades of each competency were recorded and computed to get the Mean grades in both sources to determine the level of performance of the learners before and after Project BRACE. Based on the overall interpretation of the Mean having the mean average of 4.67, the respondents’ level of acceptability of JDVP through Project BRACE is “Strongly Agree”. Therefore, the objective of the program was met. As a result of the Focused Group Discussion, most of the learner-beneficiaries mastered those given competencies set by the work immersion partner institution which are closely related to the TESDA Training Rules and Regulations.